In silico analysis identifies a C3HC4-RING finger domain of a putative E3 ubiquitin-protein ligase located at the C-terminus of a polyglutamine-containing protein - T. Scior; F. Luna; W. Koch; J.F. Sánchez-Ruiz (Brazilian Journal of Medical and Biological Research, 2007)
Almost identical polyglutamine-containing proteins with unknown structures have been found in human, mouse and rat genomes (GenBank AJ277365, AF525300, AY879229). We infer that an identical new gene (RING) finger domain of real interest is located in each C-terminal segment. A three-dimensional (3-D) model was generated by remote homology modeling and the functional implications are discussed. The model consists of 65 residues from terminal position 707 to 772 of the human protein with a total length of 796 residues. The 3-D model predicts a ubiquitin-protein ligase (E3) as a binding site for ubiquitin-conjugating enzyme (E2). Both enzymes are part of the ubiquitin pathway to label unwanted proteins for subsequent enzymatic degradation. The molecular contact specificities are suggested for both the substrate recognition and the residues at the possible E2-binding surface. The predicted structure, of a ubiquitin-protein ligase (E3, enzyme class number 6.3.2.19, CATH code 3.30.40.10.4) may contribute to explain the process of ubiquitination. The 3-D model supports the idea of a C3HC4-RING finger with a partially new pattern. The putative E2-binding site is formed by a shallow hydrophobic groove on the surface adjacent to the helix and one zinc finger (L722, C739, P740, P741, R744). Solvent-exposed hydrophobic amino acids lie around both zinc fingers (I717, L722, F738, or P765, L766, V767, V733, P734). The 3-D structure was deposited in the protein databank theoretical model repository (2B9G, RCSB Protein Data Bank, NJ).